The role of trained cadres to find new cases of leprosy with a social learning theory approach in the City of Bima, Indonesia - Kurniadi, Kurniadi; Hasbi, Muhamad (International Journal of Public Health Science (IJPHS), 2024)
The role of empowering health cadres to change their perceptions of leprosy is very important for early detection. The aim of the research is to determine the role of trained cadres to find new cases of leprosy with a social learning theory approach. The quasi-experimental method was used in this study to identify new cases of leprosy, with a sample of 20 trained cadres and 20 untrained samples as controls. The data collected were then processed using the Mann-Whitney. The distribution of leprosy case findings in the control group revealed 17 negative cases and three suspected cases, and the distribution of leprosy case findings in the treatment group revealed 12 negative cases, one suspected case, and seven positive cases. On the results of the Mann-Whitney test, it was found that the value of p=0.03 <0.05 and the difference in the mean rank of the treatment was 23.52 and the mean rank in the control was 17.48. In conclusion, there was a difference in the range of case findings between the control and treatment groups that received leprosy identification training using social learning methods. The recommendation is to explore potential factors that may contribute to the observed differences in case findings.